Determine the Deficiency of Serum Zinc Level in Children with Febrile Seizures - Sadaf Liaqat, Asima Khanam, Sajid Hussain Sherazi, Rabeya Rehman, Rabia Nisar, Maria Khalid (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the deficiency of serum zinc level in children presented with febrile seizures. Study design: Cross-sectional study Place and duration: Rai Medical College Teaching Hospital Sargodha from 1st January 2021 to 30th June 2021. Methodology: Total of 130 patients of ages 5 months to 5 years of both genders were included. Study participants were divided into group A and group B. Group A consist of 65 patients with febrile seizures and group B contained 65 patients having fever without seizures. Blood samples were collected for serum zinc examination and for the comparison between both groups. Results: There were 39(60%) males and 26 (40%) females in group A with mean age 28.25±12.6 months and 36 (55.38%) patients were males and 29(44.62%) were females with mean age 29.42±10.15 months in Group B. Significant difference between both zinc groups were noticed and the mean values were 59.50±12.88 µg/dl and 88.45±14.26 µg/dl respectively. Conclusion: Significant difference was observed and serum zinc level was significantly lower in febrile seizure children